2013
DOI: 10.1007/s00120-012-3070-8
|View full text |Cite
|
Sign up to set email alerts
|

Die Umwendungsorchidopexie zur Rezidivprophylaxe einer Hodentorsion

Abstract: On the basis of these results it may be concluded that eversion orchidopexy can be considered to be a safe and effective method for the prophylaxis of recurrent testicular torsion in comparison to alternative methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…16,19,27,29 The fixation of the tunica albuginea to the dartos muscle, as well as eversion of the tunica albuginea, has been shown, at least in the current available literature, to prevent retorsion. 45 It must be noted, however, that there is currently no available literature on the third occurrence of torsion, which may be a consequence not yet reported. Current surgical technique recommendations include orchidopexy of both testes with non-absorbable sutures with fixing of the testes via the dartos pouch or directly to the dartos pouch.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…16,19,27,29 The fixation of the tunica albuginea to the dartos muscle, as well as eversion of the tunica albuginea, has been shown, at least in the current available literature, to prevent retorsion. 45 It must be noted, however, that there is currently no available literature on the third occurrence of torsion, which may be a consequence not yet reported. Current surgical technique recommendations include orchidopexy of both testes with non-absorbable sutures with fixing of the testes via the dartos pouch or directly to the dartos pouch.…”
Section: Discussionmentioning
confidence: 98%
“…The use of non‐absorbable sutures, at three sites is recommended 16,19,27,29 . The fixation of the tunica albuginea to the dartos muscle, as well as eversion of the tunica albuginea, has been shown, at least in the current available literature, to prevent retorsion 45 . It must be noted, however, that there is currently no available literature on the third occurrence of torsion, which may be a consequence not yet reported.…”
Section: Discussionmentioning
confidence: 99%
“…Filho et al found that orchiectomy rates increased at 540 degrees, and testes were salvaged in all patients with less than 360 degrees of twist and removed in all patients with over 180 degrees of twisting [19]. Another study found that non-salvageable testicles tend to have a significantly higher degree of twisting when compared to salvageable testicles [20].…”
Section: Figure 3: Number Of Patients By the Time Period Of Presentationmentioning
confidence: 99%